Case report: Non-invasive cyto-salivary sampling and biomarker detection via ELISA versus histopathology for diagnosing oral potentially malignant disorders - Insights from a case-control study - Rebaudi, Federico; Rebaudi, Alberto; De Rosa, Alfredo; Rebaudi, Alberto Luigi; Pesce, Silvia; Greppi, Marco; Roghi, Marco; Boggio, Maurizio; Candiani, Simona; Marcenaro, Emanuela (Frontiers in Immunology, 2024)
Oral leukoplakia is classified among oral potentially malignant disorders (OPMDs) by the World Health Organization (WHO). The visual oral examination (VOE) is the most used method for identifying lesions in their early stages. Given that the diagnosis of oral cancer is often late, there is an urgent need for early detection and examination of oral lesions. Surgical biopsy represents the gold standard as a diagnostic method, but because it is invasive, it cannot be repeated for periodic checks. We report the case of a lesion on the buccal mucosa of a 65-year-old male patient with a malignant appearance. The patient underwent a novel non-invasive cyto-salivary sampling and ELISA immunoassay for tumor biomarker detection and biopsy with histopathological analysis. The rapid ELISA test results excluded signs of malignancy, providing valuable insights into the lesion’s immunophenotypic profile, which were consistent with the histopathological examination findings. This case report highlights the clinical and histopathological characteristics of a lesion with the aspect of Proliferative Verrucous Leukoplakia (PVL), emphasizing its challenging diagnosis and management. The integration of non-invasive cytobrush sampling with biomarker analysis proved valuable in detecting specific tumor biomarkers, potentially indicating ongoing tumor transformation. Monitoring these markers over time could enhance early detection and management strategies, thereby improving patient outcomes. This approach underscores the utility of non-invasive techniques in phenotyping oral lesions and supporting clinical decision-making in oral medicine.